Handbook of hormones : comparative endocrinology for basic and clinical research - Takei, Yoshio; Ando, Hironori; Tsutsui, Kazuyoshi (Academic Press, 2016)
Handbook of Hormones: Comparative Endocrinology for Basic and Clinical Research collates fundamental information about the structure and function of hormones from basic biology to clinical use. The handbook offers a rapid way to obtain specific facts about the chemical and molecular characteristics of hormones, their receptors and signalling pathways, and the biological activities they regulate. The evolution of hormones and gene families is also covered both in the text and in online ancillaries. Users will find simple and visual ways to learn key molecular information. Chapters and online ancillary resources integrate additional sections, providing a comparative molecular, functional, and evolutionary consideration.- Resumé vydavatel
"An Elsevier science & technology book."
Includes index.
Produced in association with the Japan Society for Comparative Endocrinology.
Keywords: hormony; endokrinologie -- metody; hormones; endocrinology -- methods; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals